2021
DOI: 10.1007/s00284-021-02569-8
|View full text |Cite
|
Sign up to set email alerts
|

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa

Abstract: Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Probiotics demonstrated beneficial effect on host immune response [ 48 ], although studies of the effect of probiotics on sIgA levels have shown conflicting results. Some studies found increased levels of salivary sIgA in adults [ 44 , 47 , 49 , 50 , 51 ], elderly patients [ 52 ], and children [ 47 , 48 ] after probiotic intake, while others were unable to confirm such findings [ 23 , 53 , 54 , 55 , 56 ]. One study even demonstrated a decrease in salivary sIgA after Bifidobacterium-containing probiotic intake [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics demonstrated beneficial effect on host immune response [ 48 ], although studies of the effect of probiotics on sIgA levels have shown conflicting results. Some studies found increased levels of salivary sIgA in adults [ 44 , 47 , 49 , 50 , 51 ], elderly patients [ 52 ], and children [ 47 , 48 ] after probiotic intake, while others were unable to confirm such findings [ 23 , 53 , 54 , 55 , 56 ]. One study even demonstrated a decrease in salivary sIgA after Bifidobacterium-containing probiotic intake [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings that probiotic strains of AP-32, ET-66 and LPL28 effected oral microbiota [ 23 ] and viable strains may improve salivary IgA via up-regulating anti-inflammatory cytokines, IL-10 and TGF-beta [ 35 ]. Besides, a previous animal study discovered the mixed viable probiotic strains of Lactobacillus salivarius subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics with a long history of safe use in foods or those obtained from healthy gastrointestinal tracts are unlikely to harm the human body, such as Lactobacillus species ( acidophilus , casei , fermentum , gasseri , johnsonii , paracasei , plantarum , rhamnosus , and salivarius ) and Bifidobacterium species ( adolescentis , animalis , bifidum , breve , and longum ). [ 32 ] Studies have reported various functions of B. animalis CP-9, such as inhibition of extended-spectrum β-lactamase–producing E. coli [ 33 ] ; inhibition of pathogenic group B Streptococcus , which is highly correlated with newborn survival rate [ 34 , 35 ] ; suppression of pathogenic Staphylococcus aureus , which may cause infant atopic dermatitis [ 36 , 37 ] ; protection against oral pathogens to improve oral immunity in subhealthy adults [ 38 , 39 ] ; and reduction of inflammation and glycemic index in a type 2 diabetes animal model. [ 40 ] In the present study, food-grade probiotic strain B. animalis CP-9 in synergy with phototherapy was effective in NJ treatment.…”
Section: Discussionmentioning
confidence: 99%